Bahan ajar Pendidikan Effectiveness of Electronic Student Worksheets (LKPD) Problem-Based Learning (PBL) Based on Social Scientific Problems (SSI) in Improving Problem Solving Skills - Dilla Eka Septiani; Sri Wardhani; Marlina Ummas Genisa (Jurnal Penelitian Pendidikan IPA, 2025)
Efforts to improve the quality of education can be made in various ways, one of which is the use of innovative and technology-based teaching materials. Student Worksheets (known with LKPD) are one of the learning tools used by educators to deliver material and improve student understanding. This research intended for developing electronic LKPDSSIPBL based on circulatory system material at SMAN Palembang which is valid, practical and effective.  The development model using 4D refers to Thiagarajan which goes through 4 stages, namely define, design, develop, and disseminate. The population and sample of the study included SMAN 4, SMAN 9, and SMAN 19 Palembang, while the sample of the study was 36 students of class XI.1 and 36 students of class XI.2. Data collection techniques used questionnaires and written tests. Data analysis used validity, reliability, and N-Gain. The results of this study consisted of (1) The define stage obtained a result of 41% meaning that teachers and students need SSI Electronic LKPD (2) The design stage obtained a value of 95% (3) The develop stage showed validation from language experts 83%, materials 81%, media 96%, and learning devices 83% were qualified as very feasible. Practicality, seen from student responses 82% and 2 teachers 98% and 97% showed very practical responses; (4) The dissemination stage shows that the use of PBL-based Electronic Practical Worksheets can improve critical thinking skills and problem-solving skills.